Respuesta :
[tex]answer = 14 \\ solution \\ \frac{ - 3(7 + 5)}{ {3}^{2} } + 9(2) \\ = \frac{ - 3 \times 12}{9} + 18 \\ = \frac{ - 36}{9} + 18 \\ = \frac{ - 36 + 18 \times 9}{9} \\ = \frac{ - 36 + 162}{9} \\ = \frac{126}{9} \\ = 14 \\ hope \: it \: helps \\ good \: luck \: on \: your \: assignment[/tex]
Answer:
[tex]14[/tex]
Step-by-step explanation:
[tex] \frac{ - 3(7 + 5)}{ {3}^{2} } + 9(2) \\ \frac{ - 21 - 15}{9} + 18 \\ \frac{ - 36}{9} + 18 \\ - 4 + 18 \\ = 14[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!